PorousMedia4Foam: Multi-scale open-source platform for hydro-geochemical simulations with OpenFOAM®. (November 2021) - Soulaine, Cyprien; Pavuluri, Saideep; Claret, Francis; Tournassat, Christophe
Abstract: porousMedia4Foam is a package for solving flow and transport in porous media using OpenFOAM® - a popular open-source numerical toolbox. We introduce and highlight the features of a new generation open-source hydro-geochemical module implemented within porousMedia4Foam, which relies on micro-continuum concept and which makes it possible to investigate hydro-geochemical processes occurring at multiple scales i.e. at the pore-scale, reservoir-scale and at the hybrid-scale. Geochemistry is handled by a third party package (e.g. PHREEQC) that is coupled to the flow and transport solver of OpenFOAM®. We conducted benchmarks across different scales to validate the accuracy of our simulator. We further looked at the evolution of mineral dissolution/precipitation in a fractured porous system. Application fields of this new package include the investigation of hydro-bio-geochemical processes in the critical zone, the modelling of contaminant transport in aquifers, as well as and the assessment of confinement performance for geological barriers. Highlights: We developped an open-source platform for multi-scale simulations of hydro-geochemical processes. A unique formulation can handle pore-scale, hybrid-scale and continuum-scale simulations for hydro-geochemical processes. The framework is verified using reference solutions both at the pore-scale and at continuum-scale using PHREEQC. We investigate reactive transport in a fractured porous medium at the hybrid-scale.